Body shape differences in a pair of closely related Malawi cichlids and their hybrids: Effects of genetic variation, phenotypic plasticity, and transgressive segregation - Husemann, M.; Tobler, Michael; McCauley, C.; Ding, B.; Danley, P. D. (My University, 2017)
Phenotypic differences may have genetic and plastic components. Here, we investigated the contributions of both for differences in body shape in two species of Lake Malawi cichlids using wild-caught specimens and a common garden experiment. We further hybridized the two species to investigate the mode of gene action influencing body shape differences and to examine the potential for transgressive segregation. We found that body shape differences between the two species observed in the field are maintained after more than 10 generations in a standardized environment. Nonetheless, both species experienced similar changes in the laboratory environment. Our hybrid cross experiment confirmed that substantial variation in body shape appears to be genetically determined. The data further suggest that the underlying mode of gene action is complex and cannot be explained by simple additive or additive-dominance models. Transgressive phenotypes were found in the hybrid generations, as hybrids occupied significantly more morphospace than both parentals combined. Further, the body shapes of transgressive individuals resemble the body shapes observed in other Lake Malawi rock-dwelling genera. Our findings indicate that body shape can respond to selection immediately, through plasticity, and over longer timescales through adaptation. In addition, our results suggest that hybridization may have played an important role in the diversification of Lake Malawi cichlids through creating new phenotypic variation. © 2017 Published by John Wiley & Sons Ltd.
Citation: Husemann, M., Tobler, M., McCauley, C., Ding, B., & Danley, P. D. (2017). Body shape differences in a pair of closely related Malawi cichlids and their hybrids: Effects of genetic variation, phenotypic plasticity, and transgressive segregation. Ecology and Evolution. doi:10.1002/ece3.2823
Keywords: Cichlids; Geometric Morphometrics; Lake Malawi; Local Adaptation; Phenotypic Plasticity; Transgressive Segregation